Environmental and genetic effects on phytochemical and nutritional composition of onion (Allium cepa L.) varieties in South Korea - Imran, Muhammad; Kang, Hajeong; Kim, Eun-Ha; Lee, Sang-Gu; Park, Hyun-Min; Choi, Hanyoung; Kim, Seong-Hoon; Lee, Seonwoo; Oh, Seonwoo (Frontiers in Plant Science, 2025)
Onions (Allium cepa L.) are widely recognized for their antioxidant properties, bioactive compounds such as flavonoids, organosulfur compounds (OSCs), and phenolics. This study evaluate the antioxidant activities, phytochemical composition, and nutrient variations of two onion varieties, Katamaru (KM) and Sunpower (SP), cultivated in two different locations, Muan and Changnyeong, Korea. The antioxidant activity was assessed through enzymatic and non-enzymatic parameters, including peroxidase (POD), polyphenol oxidase (PPO), ascorbate peroxidase (APX), glutathione reductase (GSH), catalase (CAT), superoxide dismutase (SOD), DPPH radical scavenging activity, and total phenolic content (TPC). The results indicated that KM consistently exhibited higher antioxidant potential than SP, with Muan-grown samples demonstrating superior enzymatic and non-enzymatic activities compared to Changnyeong. Where Muan’s alkaline soil and higher phosphorus content favored oxidative stress mitigation. Furthermore, nutrient analysis revealed significant genotype x environment interactions, affecting macronutrient (K, P, Ca, Mg, S) and micronutrient (Na, Cu, Fe, Mn, Zn) accumulation. Additionally, KM demonstrated higher amino acid composition compared to SP in both location, Muan and Changnyeong, likely influenced by environmental factors such as temperature and soil pH. The findings of this study offer insights for improving onion antioxidant and nutrient traits. These results emphasize the role of environmental adaptation and varietal selection in maximizing onion quality and potential health benefits.